Radikalisme Agama Penghambat Kemajuan Peradaban - Arif Nuh Safri (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2013)
Exclusivism in religion is one factor that is closely related to the emergence  of religious radicalism or violence. Exclusivity is also of course a poor indicator of human civilization caused by social empathy is still thin. Thus, it is clear that such a religious pattern is built with an exclusive insight anyway. Through this article, the author would like to express that violence in any form is a major obstacle in achieving an advanced civilization, or at least reach back civilization achieved by the Prophet as a carrier Muhammmad treatise. In addition, this article also emphasizes that Islam is not a religion that teaches violence exclusively.